Foliar Phenolic Antioxidant Constitution of Mallotus stenanthus - Petrus, A.J.A. (Asian Journal of Chemistry, 2010)
Cancer remains the second most abundant cause of death globally. Traditional herbal medicines possessing antioxidant potentials offer protection against several chronic and predominantly life-style oriented human diseases, including cancer. Mallotus stenanthus, which has been reported to be an anticancer agent against P388 lymphocytic leukaemia in mice, has been evaluated to possess in vitro antioxidant (ABTSˆ+ scavenging, FRAP, b-carotene bleaching) capacities and metal chelating abilities. The antioxidant capacities correlated well with the phenolic and flavonoid constitutions. The EtOAc fraction exhibited highest antioxidant capacity, 7-O-b-D-glucopyranosides of diosmetin and chrysoeriol together with ellagic acid, phloroglucinol and its derivatives have been isolated and characterized, substantiating the reported antitumour properties of the leaf extract.